Differences in physiological tolerance to global warming caused the Permian–Triassic transition between the Paleozoic and Modern faunas - J. Andres Marquez; Justin L. Penn; Richard G. Stockey; Thomas H. Boag; Murray I. Duncan; Kyra N. McClure; Kendall Matsumoto; Kemi F. Ashing-Giwa; Christopher P. Noll; Curtis Deutsch; Jonathan L. Payne; Erik A. Sperling (Proceedings of the National Academy of Sciences, 2026)
The rapid global climate change at the end of the Permian Period (~251.9 Mya) coincided with the greatest macroevolutionary faunal turnover event in Earth’s history. As the oceans warmed, lost dissolved oxygen, and became more acidic, the dominant animal groups in the Paleozoic fauna (including brachiopods and crinoids) suffered differentially high rates of extinction, allowing the Modern fauna (including bivalves and gastropods) to rise to ecological dominance. The end-Permian kill mechanism(s) are not fully understood, but differences in extinction intensity among Linnaean classes suggest an important physiological component. Here, we use a trait-based model of species’ metabolic O 2 balance to demonstrate that temperature-dependent hypoxia can explain the taxonomic selectivity of the end-Permian mass extinction. Direct respirometry experiments and physiological trait estimates derived from biogeographic data reveal that species belonging to the Paleozoic fauna have a higher temperature dependence of hypoxia than those belonging to the Modern fauna. In simulations of the climate transition, this trait difference leads to a greater loss of aerobic habitat for Paleozoic fauna, consistent with their observed greater extinction intensity. These results demonstrate that differences in average physiological tolerances to environmental change across biogeography, taxonomy, and functional ecology drove end-Permian extinction patterns and could eventually characterize the modern biodiversity crisis. Temperature-dependent hypoxia is the only kill mechanism that has been shown to explain the magnitude, biogeography, and now taxonomic selectivity of the end-Permian mass extinction, ultimately underlying the permanent shift in marine ecosystems across this transition.